Hyponatremia misdiagnosed as depression - Neena S Sawant; Shubhangi R Parkar; Karishma Rupani; Himanshi Bansal; Suraj Singh (Annals of Indian Psychiatry, 2019)
Serotonin reuptake inhibitors, antiepileptics, and antipsychotics are frequently used drugs by psychiatrists for various psychiatric illness which have hyponatremia as a side effect. The symptoms of hyponatremia include lethargy, weakness, headache, and irritability with neuropsychiatric complications such as seizures and confusion. Symptoms of hyponatremia usually occur when serum sodium concentration falls below 130 mEq/L. We report two cases which presented with depressive symptoms but were found to have persistent low serum sodium levels. The depressive features further improved on sodium correction. Both patients were on drugs which caused hyponatremia, a commonly occurring side effect of many medications which often goes undiagnosed. The cases highlight the importance and need for regular evaluation and monitoring.